The techno-politics of programming vision. - Amin, Heba Y.; Downey, Anthony (Visual Studies)
The article presents a conversation on the techno-politics of programming vision and explores the interdisciplinary relationship between art practices and academic research. Topics include the histories of image-making technologies and post-digital and neo-colonial models of representation; colonial exploitation; and data extraction from images.